Reperfusion Therapy in Acute Stroke: State-of-the-Art and Future Directions - Vinall, Phil (MD Conference Express, 2009)
Reperfusion therapy with IV rt-PA and recanalization produces good outcomes in patients with acute stroke, but challenges remain. It is estimated that 85% of all ischemic strokes are not treated with thrombolysis; thus, improved and early access to treatment is needed. It is suggested that the 3 to 6-hour time window for treatment may be extended by better patient selection criteria using transcranial Doppler markers of the diffusion-perfusion mismatch method [Restrepo L et al. J Neuroimaging 2006] and combination therapies, such as reduced-dose rt-PA plus eptifibatide [Pancioli AM et al. Stroke 2008] or rt-PA plus GPIIb/IIIa antagonists.